National-scale river water quality in the Philippines: establishing baselines in a mineralised megadiverse nation - Emma Biles; Richard David Williams; Decibel Faustino-Eslava; Loucel Cui; Francis Ian Gonzalvo; Kim Bryan Cabrera; Manilyn Casa; Craig MacDonell; Maria Regina V. Regalado; Laura Quick; Justine Perry Domingo; Trevor Hoey; et al. (Science of The Total Environment, 2026)

Let the riverscape grow! Riverscape rewilding restores lateral connectivity and promotes geomorphic recovery in a Scottish gravel-bed river - Lucy J. Daniels; Richard D. Williams; Maggie J. Creed; Laura Quick; Craig J. MacDonell; Hamish Moir; Kenny Roberts (Science of The Total Environment, 2026)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Detection of Potato Mop-Top Virus in Potato Seed Lots Entering Washington State - Kylie D. Swisher Grimm; Richard A. Quick; Launa Cimrhakl; Charles Brown; Mark J. Pavek (American Journal of Potato Research, 2022)

Resistance to Meloidogyne chitwoodi Identified in Wild Potato Species - Ryan C. Graebner; Charles R. Brown; Russell E. Ingham; Christina H. Hagerty; Hassan Mojtahedi; Richard A. Quick; Launa L. Hamlin; Nadine Wade; John B. Bamberg; Vidyasagar Sathuvalli (American Journal of Potato Research, 2018)

Large-scale invasion of western Atlantic mesophotic reefs by lionfish potentially undermines culling-based management - Dominic A. Andradi-Brown; Mark J. A. Vermeij; Marc Slattery; Michael Lesser; Ivonne Bejarano; Richard Appeldoorn; Gretchen Goodbody-Gringley; Alex D. Chequer; Joanna M. Pitt; Corey Eddy; Struan R. Smith; Eran Brokovich; et al. (Biological Invasions, 2017)

“AmaRosa,” a Red Skinned, Red Fleshed Fingerling with High Phytonutrient Value - Charles R. Brown; Isabel Vales; Solomon Yilma; Steven James; Brian Charlton; Darrin Culp; Dan Hane; Clinton Shock; Eric Feibert; Mark Pavek; Richard Knowles; Richard Novy; et al. (American Journal of Potato Research, 2012)

Partial Resistance to Potato Black Dot, Caused by Colletotrichum coccodes in Solanum tuberosum Group Andigena - Nadav Nitzan; Richard A. Quick; Will D. Hutson; John Bamberg; Chuck R. Brown (American Journal of Potato Research, 2010)